PELATIHAN PENGGUNAAN ALAT PEMERAS SANTAN DAN MESIN PENGUPAS SABUK KELAPA PADA BUMDES SUMBER BERKAT DESA MARINSOW - Sanjaya, Ricardo; Sidik, Dilan Richardo; Somba, Junri; Alfredo, Jannifer; Sarubang, Gabriel Vieri Sarubang; Moningka, Gregorius Viktor; Simbolon, Efriwandy; Sthiefandy, Alvin; sinaga, Amos Axcel; Pomalingo, Moh. Fikri; Bandu, Rahmat; Pabubung, Kurnia; Silalahi, Rike Firda; Situmorang, Ayu Triana; Sinaga, Ramesintia; Saerang, Syefiorita Angela; Zega, Cici Chrisdayanti (Abdi Techno, 2024)
Decree of the President of the Republic of Indonesia, Likupang became one of the priority tourist destinations. This is certainly a blessing for the people of North Sulawesi, especially Likupang. One of the industries in Marinsow Village is producing klentik coconut oil (village oil). Klentik coconut oil (village oil) is a product derived from coconuts. This oil has a distinctive taste and aroma for the fish meat that will be served. This product is also one of North Sulawesi's export commodities. In the process of making klentik coconut oil, there are several stages that must be passed. These stages include, peeling the coconut, splitting the coconut, grating the coconut meat, making coconut milk, stirring, fermenting, separating and cooking. Based on the results of the team's interviews with partners, several problems were raised. These problems include, 1) the equipment used is still traditional, 2) peeling coconut is still manual and takes a lot of time and energy, 3) the process of separating oil and water in coconut milk still takes 12-15 hours, 4) there is no business management and 5) the product is not yet standardized. The methods used in this activity are surveys, tool manufacturing, machine use training and reporting. From the results obtained, the participants were very enthusiastic about taking part in the training as evidenced by the presence of the participants. As a result of the interviews, the training participants were able to explain orally the components that make up the tools 80% of the time. The presentation value was not optimal, because there were 2 people aged 56 and 60 years. Both of them were unable to remember and were shy in explaining. For practical material, all participants with a percentage of 100% were able to process coconut milk using a homogeneizer machine or coconut peeling